2022
DOI: 10.12928/fokus.v12i2.6665
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompensasi, Kepuasan Kerja, Dan Stres Kerja Terhadap Turnover Intention

Abstract: The success of an organization can be portrayed by the employee turnover intention rate each month. Employee turnover intention can be influenced by compensation, job satisfaction, and work stress. The purpose of this study is to test and analyze the relationship among compensation factors, job satisfaction, and work stress on employees at PT. Tanjung Kreasi Parquet Industri (TKPI). This study was conducted in a Quantitative research method with multiple regression analysis. The population of this study was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…In this context, it can be inferred that higher levels of compensation tend to reduce employees' intentions to seek employment elsewhere. These results are consistent with earlier studies, including studies conducted by (Putri & Anisa, 2022) This aligns with prior research, including studies that have also observed a negative impact of compensation on turnover intention.…”
Section: Compensation's Relationship To Turnover Intentionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this context, it can be inferred that higher levels of compensation tend to reduce employees' intentions to seek employment elsewhere. These results are consistent with earlier studies, including studies conducted by (Putri & Anisa, 2022) This aligns with prior research, including studies that have also observed a negative impact of compensation on turnover intention.…”
Section: Compensation's Relationship To Turnover Intentionsupporting
confidence: 92%
“…According to (Fitriani & Yusiana, 2020;Meiliawati Ratri et al, 2022;Putri & Anisa, 2022), In the findings derived, it is evident that compensation exerts a noteworthy negative impact on turnover intention. Based on this examination, the authors propose:…”
Section: Hypothesis Development a Compensation On Turnover Intentionmentioning
confidence: 97%
See 1 more Smart Citation
“…The desire to shift employment (turnover intention) is defined by Siagian (2012) as a person's desire to quit the organization where he works. According to Harnoto (2002) in Putrianti et al (2014), turnover intention is defined as "the level or intensity of the desire to leave the company, many reasons that cause this turnover intention, one of which is the desire to get a better job." This viewpoint is similar to the last one in that turnover intention is essentially the desire to depart or leave the firm.…”
Section: Turnover Intentionmentioning
confidence: 99%